CRISPR Cas13-Based Tools to Track and Manipulate Endogenous Telomeric Repeat-Containing RNAs in Live Cells - Xu, Meng; Chigumira, Tafadzwa; Chen, Ziheng; Tones, Jason; Zhao, Rongwei; Dahl, Kris Noel; Chenoweth, David M.; Zhang, Huaiying (Frontiers in Molecular Biosciences, 2022)
TERRA, TElomeric Repeat-containing RNA, is a long non-coding RNA transcribed from telomeres. Emerging evidence indicates TERRA regulates telomere maintenance and chromosome end protection in both normal and cancerous cells. But the mechanism of how TERRA contributes to telomere functions is still unclear, partially owing to the shortage of approaches to track and manipulate endogenous TERRA molecules in live cells. Here, we developed a method to visualize TERRA in live cells via a combination of CRISPR Cas13 RNA labeling and Suntag technology. Single-particle tracking reveals that TERRA foci undergo anomalous diffusion in a manner that depends on the timescale and telomeric localization. Furthermore, we used a chemically-induced protein dimerization system to manipulate TERRA subcellular localization in live cells. Overall, our approaches to monitor and control TERRA locations in live cells provide powerful tools to better understand its roles in telomere maintenance and genomic integrity.